Prevalence of hypertension among antiretroviral therapy naïve patients in Lagos, Nigeria - Oluwatosin Odubela; Nkiruka Odunukwe; Nasheeta Peer; Adesola Zaidat Musa; Babatunde Lawal Salako; Andre Pascal Kengne (BMC, 2023)
Abstract Background The gains from successful antiretroviral therapy (ART) roll-out could be compromised by the increasing burden of non-communicable diseases, particularly cardiovascular diseases among people living with HIV (PLWH). Hypertension remains a significant contributor to cardiovascular diseases. This study aims to determine the prevalence and determinants of hypertension among ART-naïve PLWH in a large ART clinic in Lagos, Nigeria. Materials and methods This study uses data collected from adult ART-naïve PLWH enrolled at an ART clinic over ten years. Participants aged 18 years and older, not pregnant, and not accessing care for post-exposure prophylaxis were included in the study. Hypertension was defined as systolic and diastolic blood pressure greater than or equal to 140 mmHg and 90 mmHg, respectively. Logistic regressions were used to investigate the factors associated with hypertension. Results Among the 10 426 participants included in the study, the majority were females (66%) and aged 25-49 years (84%). The crude prevalence of hypertension was 16.8% (95%CI 16.4 - 17.2) while the age and sex standardised prevalence rate was 21.9% (95%CI 20.7 - 23.2), with males (25.8%, 95%CI 23.5 - 28.0) having a higher burden compared with females (18.3%, 95%CI 17.0 - 19.6). Increasing age, male gender, overweight or obesity, co-morbid diabetes mellitus or renal disease, and CD4 count ≥ 201 cells/μL were significantly associated with prevalent hypertension. Conclusion There was a substantial burden of hypertension among ART-naïve PLWH, which was associated with the traditional risk factors of the condition. This highlights the need to integrate screening and care of hypertension into routine HIV management for optimal care of PLWH. Graphical Abstract